FORECASTING OF NEW CASES OF TB, USING BOX-JENKINS APPROACH - MUHAMMAD IMRAN; JAMAL ABDUL NASIR; SYED ARIF AHMED ZAIDI (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: Prediction through mathematical models allows us to better understand the development and the pattern of fatal diseases, a significant concern in the adaption of preventative measures. This study therefore aimed to uncover the trend and forecast the new TB incidences for the major districts of Punjab province, placed first in term of population as compared to other provinces of Pakistan. METHODS: The relevant data from 2001 to 2011 for the present study has been taken from the National TB Control program Ministry of National Health Service Government of Pakistan, Islamabad. A univariate modelling is used by taking Xt= (the number of new TB cases per quarter of four districts, namely Bahawalpur, Attock, Lahore and Rawalpindi were averaged) the total time series entities were 44. RESULTS: The main purpose of this study is to develop a forecasting model by incorporating the Box-Jenkins methodology for the new cases of Tuberculosis in major district of Punjab, Pakistan. Twenty four different ARIMA models have been attempted to forecast new cases of TB. Three measures namely Akaike, Hannan-Quinn and Schwarz are used to identify the efficient models. The final selected model, ARIMA (3, 1, 0) revealed the increment of new TB cases in major districts of Punjab—say for a 100 cases in 2011, 11 new cases are expected in 2012. CONCLUSION: A rising trend is expected in TB new cases in various districts of Punjab.